Pengembangan Sistem Informasi Presensi Berbasis Global Positioning Systems dan Location-Based Service - Utomo, Prabowo Budi; Wahyudi, Dona; Mujiono, M (LPPM STT Terpadu Nurul Fikri, 2025)
This study focuses on the development of an attendance system based on the Global Positioning System (GPS) and Location-Based Service (LBS) using the Extreme Programming (XP) approach. This system helps institutions and companies enhance the accuracy and efficiency of employee attendance recording, particularly for mobile workers such as field employees or operational staff. The implementation of this system aims to overcome the limitations of conventional attendance methods, which are prone to manipulation, such as proxy attendance or multiple fingerprint recognition usage, as well as difficulties in accessing attendance data for auditing and performance evaluation purposes. GPS technology determines the user's real-time location, while LBS enhances the accuracy and reliability of location data. This study chooses the XP methodology due to its flexibility and adaptability to changing requirements during development. Testing results indicate the system achieves a 91.4% success rate in recording attendance with accurate location validation. The system is compatible with various devices and operational conditions, offering high flexibility in its implementation. However, challenges remain regarding external factors such as geographical conditions, weather, and device quality, which may affect location accuracy. Overall, this system offers a transparent, accurate, and efficient attendance solution.